Image-derived instrumentation vs. conventional instrumentation with 3D planning for glenoid component placement in reverse total shoulder replacements: a randomized controlled trial - Pamela Boekel, MBBS (Hons), MSc; Matthew Rikard-Bell, MBBS; Andrea Grant, BSpExSci; Benjamin Brandon, MBBS; Kenji Doma, PhD; William B. O’Callaghan, MBBS; Matthew Wilkinson, MBBS; Levi Morse, BMBS (Hons) (JSES International, 2023)
Hypothesis: Glenoid baseplate positioning for reverse total shoulder arthroplasty (rTSA) is important for stability and longevity, with techniques such as image-derived instrumentation (IDI) developed for improving implant placement accuracy. We performed a single-blinded randomized controlled trial comparing glenoid baseplate insertion accuracy with 3D preoperative planning and IDI jigs vs. 3D preoperative planning and conventional instrumentation. Methods: All patients had a preoperative 3D computed tomography to create an IDI; then underwent rTSA according to their randomized method. Repeat computed tomography scans performed at six weeks postoperatively were compared to the preoperative plan to assess for accuracy of implantation. Patient-reported outcome measures and plain radiographs were collected with 2-year follow-up. Results: Forty-seven rTSA patients were included (IDI n = 24, conventional instrumentation n = 23). The IDI group was more likely to have a guidewire placement within 2mm of the preoperative plan in the superior/inferior plane (P = .01); and exhibited a smaller degree of error when the native glenoid retroversion was >10° (P = .047). There was no difference in patient-reported outcome measures or other radiographic parameters between the two groups. Conclusion: IDI is an accurate method for glenoid guidewire and component placement in rTSA, particularly in the superior/inferior plane and in glenoids with native retroversion >10°, when compared to conventional instrumentation.